The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1080/10496491.2018.1536623
|View full text |Cite
|
Sign up to set email alerts
|

Has Advertising Lost Its Meaning? Views of UK and US Millennials

Abstract: The findings of a study of Millennials in USA and the UK-an increasingly important and digitally savvy segment of consumers-reveal that they see advertising as Companies promoting a product or service to people through media. Their perception is simple and all-encompassing with no evidence that they distinguish between different types of media or different types of communication. Some variation between the views of Millennials in the two countries is also identified, although this is less than expected. The fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 22 publications
0
1
0
3
Order By: Relevance
“…This blurring of the role of the different marketing communication tools has led to the situation where it is questionable whether consumers can or should be able to differentiate between them. A study by Laurie et al (2019) found that U.S. and U.K. Millennials did not differentiate between different types of communication and perceived marketing communications activity just as “promotion.” This links to the idea proposed by Finne and Gronroos (2017) who state that much of the integration of messages is actually undertaken by the customer, referred to as communication-in-use. They acknowledge that social media plays a big part in this merging of messages and that the classification by the industry of different types of communication activity is irrelevant to the customer.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This blurring of the role of the different marketing communication tools has led to the situation where it is questionable whether consumers can or should be able to differentiate between them. A study by Laurie et al (2019) found that U.S. and U.K. Millennials did not differentiate between different types of communication and perceived marketing communications activity just as “promotion.” This links to the idea proposed by Finne and Gronroos (2017) who state that much of the integration of messages is actually undertaken by the customer, referred to as communication-in-use. They acknowledge that social media plays a big part in this merging of messages and that the classification by the industry of different types of communication activity is irrelevant to the customer.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Na academia, vários autores apontam para a necessidade de uma nova definição, baseada em ângulos específicos. Os académicos estão à procura dos seus elementos essenciais (Richards & Curran, 2002), devido aos (novos) meios e formatos, bem como aos (novos) comportamentos dos "consumidores" (Dahlen & Rosengren, 2016) ou à forma como a publicidade deve ser definida no atual ambiente multicanal, tendo em conta a perspetiva dos milennials (Laurie et al, 2019).…”
Section: Discursos Dominantes Na Atual Autorregulaçãounclassified
“…Por exemplo, os millennials veem a publicidade como "empresas que promovem um produto ou serviço às pessoas através dos média" (Laurie et al, 2019, p. 765). A sua perceção é simples e abrangente, sem qualquer evidência de que consigam distinguir entre diferentes tipos de média ou diferentes tipos de comunicação (Laurie et al, 2019). Esta evidência é bastante perturbadora porque, para estas gerações, a publicidade não é uma disciplina clara.…”
Section: Discursos Dominantes Na Atual Autorregulaçãounclassified
“…Sikap kegemaran pengguna terutamanya pengguna Milenial merupakan jalan kepada kejayaan sesebuah pengiklanan. Pandangan mereka sangat penting kerana golongan Milenial merupakan segmen yang berkembang dalam persekitaran digital ini dan merupakan pasaran generasi terbesar di dunia dengan kuasa pembelian yang besar (Laurie, Mortimer & Beard, 2019;Fry, 2016).…”
Section: Pengenalanunclassified